Differential socio-demographic patterns in Bogota and Cali from the 2005 census and the presence of black middle classes in the two cities - Urrea Giraldo, Fernando; Botero-Arias, Waldorf (Sociedad y Economía, 2010)
The paper analyzes from the sociodemographic characteristics of Bogota and Cali, through Census 2005 data available, in seven local areas and six districts of the two cities, the presence of black middle classes. For this purpose are considered middle classes the groups of the population who havereached undergraduate and graduate university studies, to the granting of liberal professions or like high skill employees, which both are associated with important changes in sociodemographic profiles of these sectors, that show modernity processes. By linking demographic data with the variable of ethnic-racial self-recognition, which it was introduced by the census, it is possible to observe black population residing in these urban areas whose demographic patterns are corresponding to the middle class.